Evaluation on Soil Hardness in Riparian Forest Restoration along Kayan Ulu River, Sarawak, Malaysia - Aina Nadia Najwa, Mohamad Jaffar; Mohd Effendi, Wasli; Mugunthan, Perumal (UNIMAS Publisher, 2018)
Soil hardness plays a vital role in evaluating the physical properties of soil structure. With regards to the impact of compaction on practical forest management issues, most report and review forms were available. Thus, the aim of this study was to evaluate the soil condition in riparian forest restoration planted with indigenous species along Kayan Ulu River with special reference to soil hardness. Soil hardness was measured by using Hasegawa-type cone penetrometer from the surface soils to 100 cm depth, with a total of 48 random points for both study sites surveyed; restoration sites planted with Shorea macrophylla in year 1996 and 1998 (SPD96 and SPD98, respectively) for both on and between planting lines. Our findings indicated that, soil hardness in SPD98 was harder as compared to SPD96 at shallow depth presented in one drop penetrability. Likewise, soil penetration resistance on pla ting line in SPD98 was significantly higher than SPD96 at surface soils (0-20 cm) and subsurface soils (20-40 cm). A high number of strikes and soil penetration resistance indicate that the soils were highly compacted. However, there was no significant difference in term of soil penetration resistance between planting line. In order to avoid effects on tree productivity, it is recommended that in future, the evaluation of soil hardness should be determined during the early establishment for future restoration of riparian ecosystem.